Utilization of Catfish Body Fat in the Diet of Tilapia Oreochromis niloticus - Mia Setiawati; C. Nuraeni; D. Jusadi (Jurnal Akuakultur Indonesia)
This experiment was conducted to evaluate the effect of catfish body fat in the diet on the growth of tilapia Oreochromis niloticus. Twenty fishes with an initial body weight of 5.0±0.03 g were cultured in 100-ℓ rectangular aquaria for 58 days.  The fishes were fed on the diet contained lipid from catfish at a dosage of  either 0, 1.5, 3, 4.5 or 6%.  The results showed that lipid dosage in the diet insignificantly affected feed efficiency, (73.25-81.96%), protein retention (45.57-51.56%), daily growth rate (4.05-4.29%), and survival rate of fish (98.33-100%).  However, n-3 fatty acids of fish muscle elevated as the dosage of body fat of catfish in the diet increased. Therefore, it can be concluded that lipid from catfish can be used as a fat source in the diet of tilapia.